New records of the bee genus Colletes Latreille 1802 (Hymenoptera: Apoidea: Colletidae) in Ethiopia with description of a new species - Kuhlmann, Michael (Zootaxa, 2020)
New records of the Ethiopian species of the bee genus Colletes are presented. Colletes meneliki sp. n. is described as new and C. michaelis Cockerell 1936 is first recorded for the country and redescribed, thus bringing the number of Colletes species known from Ethiopia to ten. Also, a key is provided to enable their identification.